Kemampuan Bahasa Jepang Dasar Mahasiswa Dalam Literasi Membaca Dengan Bacaan Menggunakan Visualisasi Gambar - Masilva Raynox Mael; Didik Nurhadi; Kisyani Kisyani; Mintowati Mintowati (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
Students' reading literacy in this case understanding, reflecting, and retelling a reading is one of the factors to determine the level of language mastery for foreign language students. This study, it is discussed the basic Japanese language skills of first-year students of the Japanese Language Education study program, Surabaya State University associated with their Japanese reading literacy using Japanese reading with topics about mythical animals in Indonesia equipped with image visualization. The purpose of this study was to determine the level of basic Japanese mastery of students in terms of understanding and retelling readings based on JF Standards. The method in this research is descriptive qualitative, whose data is taken from a questionnaire on self-evaluation distributed to 25 students in the Shokyu Dokkai course. From the results of this study, it is known that the Japanese language skills of these first-year students based on the JF Standard are on average at level A2. With this result, it is hoped that it can be used as a reference for treatment in further learning